2019
DOI: 10.1002/arcp.1052
|View full text |Cite
|
Sign up to set email alerts
|

Beyond outcomes: How regulatory focus motivates consumer goal pursuit processes

Abstract: This article reviews the current state of the regulatory focus literature as it relates to consumer behavior, with a special emphasis on the goal pursuit processes that naturally align with the promotion and prevention systems. Because most research on such processes has taken place within the framework of regulatory fit theory, we highlight regulatory fit findings. We also suggest practical implications of these goal pursuit processes for marketing and branding. We then shift our attention to the standards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 75 publications
0
49
0
1
Order By: Relevance
“…Though past research has examined various factors that may influence people’s susceptibility to the numerosity heuristic (e.g., Bagchi & Davis, 2016; Bourdin & Vetschera, 2018), existing literature has not examined how individuals’ goals may also matter. This is despite much research documenting the impact of regulatory goals on a wide variety of consumption contexts (Higgins et al, 2020). The two streams of research have evolved fairly independently till now, and to the best of our knowledge, the present research is the first to integrate these two streams of research and document the effect of regulatory goals on the effectiveness of temporal framing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though past research has examined various factors that may influence people’s susceptibility to the numerosity heuristic (e.g., Bagchi & Davis, 2016; Bourdin & Vetschera, 2018), existing literature has not examined how individuals’ goals may also matter. This is despite much research documenting the impact of regulatory goals on a wide variety of consumption contexts (Higgins et al, 2020). The two streams of research have evolved fairly independently till now, and to the best of our knowledge, the present research is the first to integrate these two streams of research and document the effect of regulatory goals on the effectiveness of temporal framing.…”
Section: Discussionmentioning
confidence: 99%
“…In a political setting, Pedersen (2019) found that people on right (vs. left) of the political spectrum in the Netherlands perceived the size of unemployment benefits to be larger when it was framed in aggregate (vs. periodic) terms. Building on this stream of research, we aim to show that consumers’ regulatory goals—a factor central to a wide range of consumer decisions (Higgins et al, 2020)—may also exert a consequential impact on whether they would be susceptible to the temporal framing effect.…”
mentioning
confidence: 99%
“…The regulatory fit increased the persuasiveness of and agreement with the messages. Effects aligned with regulatory fit have been documented in various contexts, whether non-profit (e.g., health communication; Ludolph & Schulz, 2015) or for-profit (e.g., consumer research; Higgins, Nakkawita, & Cornwell, 2020;Motyka et al, 2013), and at various levels, whether individual or collective (e.g., organizational psychology; Higgins & Pinelli, 2020).…”
Section: The Role Of Regulatory Fit In Communication About a Degrowthmentioning
confidence: 99%
“…Conversely, promotion-focused individuals would see this as a missed chance to improve the situation (a non-gain), therefore considering it a failure [32]. Notably, these systems are independent, i.e., a person can be high or low on both at the same time, and while one might have a predominant disposition, regulatory focus is also affected by one's current situation [33].…”
Section: Regulatory Focus Theory 221 Outcomes and Strategiesmentioning
confidence: 99%